Caracterização mineralogica do agregado obtido a partir da lama vermelha do processo bayer - REIS, André Wilson da Cruz (Universidade Federal do Pará, 2017)
The industrial activities increasingly generate a lot of waste and by-products being stored in the environment, with physicochemical characteristics which can most often be reused. The red mud residue from the Bayer process, is being studied for use in the production of synthetic aggregates, which aims to replace natural aggregates used in construction. This work studies the physical, chemical and mineralogical characteristics of the aggregates synthesized from a mixture of red mud, clay, sand and charcoal in 4 compositions, varying amounts of red mud and clay. The raw materials were pretreated and analyzed by X-ray fluorescence, X - ray diffraction, thermal and particle size analysis. The samples were calcined at 1200 °C for 4 hours. Then subjected to analysis by X-ray diffraction, X- ray fluorescence, differential thermal analysis and scanning for characterization and physical tests electron microscopy. For the study of the observation of synthetic mullite aggregate specimens embedded in resin, and adding 5% HF for 3 to 4 minutes were made. The material presented after sintering, apparent specific gravity average below 2 g\cm3 main crystalline phases by XRD quartz and hematite and the presence of mullite from the HF treatment can be observed.